Antireticulin antibody: Incidence and diagnostic significance. Issue 4 (April 1973) - Seah, P. P.; Fry, Lionel; Holborow, E. J.; Rossiter, Mary A.; Doe, W. F.; Magalhaes, A. F.; Hoffbrand, A. V.
Abstract : Sera from 101 patients with adult coeliac disease, 46 patients with childhood coeliac disease, 50 patients with dermatitis herpetiformis, and 479 patients with various other diseases, including skin, gastrointestinal, haematological, and immunological disorders, have been tested for the presence of the antireticulin antibody. Positive sera were retested at higher dilutions. Antireticulin antibody was only found in a significant proportion of patients with three diseases, ie, coeliac disease, dermatitis herpetiformis, and Crohn's disease. Antireticulin antibody was present in 38 out of 101 patients (38%) with adult coeliac disease, 27 out of 46 patients (59%) with childhood coeliac disease, 11 out of 50 patients (22%) with dermatitis herpetiformis, and nine out of 38 patients (24%) with Crohn's disease. In the 434 other patients with various disorders the antireticulin antibody was present in only six 1·4%) (two patients were pregnant, one had vitiligo, one had tropical sprue, one had reticulum cell sarcoma, and one had pernicious anaemia). In patients with gluten-sensitive enteropathy, ie, coeliac disease and dermatitis herpetiformis, there was a significantly higher incidence in patients taking a normal diet compared with those on a gluten-free diet. The presence of antireticulin antibody would appear to be particularly helpful in diagnosing childhood coeliac disease as it was found in 22 out of 26 patients (85%) taking a normal diet.